Experimental On Sulfur Reduction Process For Waste Product And Biodiesel Fuel - Sahrudin, Intan Norshalina (Universiti Sains Malaysia, 2018)
This research is made to solve a problem of the high sulfur content in the lower grade biodiesel fuel such as the crude palm oil, waste cooking oil, and waste engine oil. High sulfur content in the biodiesel fuel that used in diesel engine may affect the environment as the sulfur dioxide (SO2) is emitted to the surrounding when combustion occur. To solve this problem, a process that able to reduce sulfur content in a lower grade biodiesel fuel which is the vacuum distillation process is developed. An Elemental Analyzer test is made to quantify the sulfur content in the product of distillation. From the result, the sulfur content in the waste engine oil is reduced as much as 11.95 % while the others have the negative result. This proved that, the vacuum distillation process has reduced the sulfur content of more than 10% of its original value. To quantify the calorific value, Bombcalorimeter testing is conducted on the distillation product. The result shown, the Higher Calorific Value (HCV) is increased about 0.82 % for crude palm oil (CPO) while 0.19 % for waste engine oil and for waste cooking the result shows the negative value. Thus, the sulfur can be removed in the waste engine oil by the vacuum distillation process as it has a positive result of Elemental Analysis and Bombcalorimeter testing. This study can be improved by adding other processes such as the acid washing, solvent extraction, esterification, and transesterification in biodiesel production to make sure more sulfur is removed.